Could adjuvants serve as an agroecological tool? - Brankov, Milan; Simić, Milena; Vukadinović, Jelena; Zarić, Miloš; Tataridas, Alexandros; Božinović, Sofija; Dragičević, Vesna (Frontiers in Agronomy, 2025)
Adjuvants are agrochemicals or natural substances, commonly mixed with pesticides to increase their efficacy or reduce off-target movement by modifying the physical properties of the spray solution, such as surface tension, droplet size, and spreadability, which ultimately improve pesticide adhesion and coverage on target surfaces. Adjuvant use across Europe remains less widespread compared to regions like the USA, where adjuvants are often recommended or required with certain herbicide applications. This paper highlights the potential benefits of incorporating adjuvants with herbicides in weed control, particularly as a strategy to reduce overall herbicide use. Findings from dose-response research on available adjuvants suggest they may enable the application of lower herbicide rates than typically recommended, without sacrificing effectiveness, thereby contributing to the goal of reducing herbicide use by 50% by 2030 in Europe. Furthermore, literature findings indicate that adjuvants significantly improve weed control by enhancing the performance of active ingredients, with efficacy increases of up to 50% compared to using herbicides alone. The integration of adjuvants into herbicide tank mixtures offers considerable promise, especially for managing herbicide-resistant weeds and achieving effective weed control.